Pengembangan Objek Wisata Air Terjun Guruh Gemurai di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi Berdasarkan Sisi Permintaan dan Ketersediaan Sarana Prasarana Wisata - Betti Mailizar; ahyuni .; ratna wilis (JURNAL BUANA, 2018)
The research aim to find out about (1) demand at atractions Guruh Gemurai Waterfall (2) availability of facilities and instructures at Guruh gemurai Waterfall. Type of research in the form of mixing method that is merging qualitative research method and quantitative research. Research subject s consist of respondents and research informants. Data collection technique by interview, observation and questionnaire and documentation. While the technique of data analysis with descriptive qualitiative, quantitativeand SWOT analysis. The result of research as follows: (1) the condition of natural tourist attraction in Guruh Gemurai Waterfall is in accordance with the wishes of tourist (2) the condition and availability of existing facilities and infrastructure is not in accordance with the wishes of the tourist (3) the development of Guruh Gemurai Waterfall object, among others, to improve the quality of tourism and maximize the attractiveness of tourism, create a special webste waterfall Guruh Gemurai, improve the quality of human resources existing Guruh Gemurai Waterfall tourism location, innovate to develop more good, build cooperation with related parties such as government and society in the effort to maintain and develop Guruh Gemurai Waterfall.